Managing Intellectual property in Digital Libraries. Chapter Title: Open access to knowledge and challenges in digital libraries. - Ouma, Cary, Francis; Nyambala, Joyce (My University, 2022)
The recent developments in Information and Communication Technologies (ICTs) have profoundly impacted modern information and knowledge management dynamics. In particular, the internet and the World Wide Web (WWW) have redefined the different aspects o scholarly communication and the role of its stakeholders. Among the emerging realities from these paradigm shifts are the open access and digital library phenomena. As the world embraces these phenomena there are emerging issues and challenges, chief amongst these are the barriers imposed by the copyright acts to free access to information. This chapter gives a detailed understanding of open access as an aspect of digital libraries and further explores the existing strategies for dealing with the copyright issues. It is based on desktop study of the available literature. It concludes that the future of scholarly communication rests with open access content, which will constitute the bulk of scholarly output and a formidable pillar of digital libraries. In this recognition, different players have come up with successful interventions for dealing with the barriers posed by copyright requirements. The chapter recommends that all the players in the scholarly communication sector should fully embrace open access principles at their levels and that stakeholders should urgently relook at the challenges posed by copyright to the realization of open access.
Keywords: digital libraries and copyright; open access